2015
DOI: 10.1097/mib.0000000000000568
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Breathing, Movement, and Meditation on Psychological and Physical Symptoms and Inflammatory Biomarkers in Inflammatory Bowel Disease

Abstract: In patients with IBD, participation in the BBMW was associated with significant improvements in psychological and physical symptoms, quality of life, and C-reactive protein. Mind-body interventions, such as BBMW, which emphasize Voluntarily Regulated Breathing Practices, may have significant long-lasting benefits for IBD symptoms, anxiety, depression, quality of life, and inflammation. BBMW, a promising adjunctive treatment for IBD, warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 33 publications
4
92
0
8
Order By: Relevance
“…Our results were similar to those published by Gerbarg et al in which patients with IBD that followed a Breath-Body-Mind Workshop showed lower levels of FC and CRP compared with those in the control group 41 . These authors suggest that bidirectional gut-brain inter-communication with the neural, hormonal, and immune www.nature.com/scientificreports www.nature.com/scientificreports/ system, among others is likely the mechanism underlying this association 42,43 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results were similar to those published by Gerbarg et al in which patients with IBD that followed a Breath-Body-Mind Workshop showed lower levels of FC and CRP compared with those in the control group 41 . These authors suggest that bidirectional gut-brain inter-communication with the neural, hormonal, and immune www.nature.com/scientificreports www.nature.com/scientificreports/ system, among others is likely the mechanism underlying this association 42,43 .…”
Section: Discussionsupporting
confidence: 92%
“…More recent work has also highlighted the function of gut microbiota in IBD as well as patient responses to probiotics. In contrast, the role of psychological stress in IBD remains controversial, even though stress and/or traumatic early-life events are known risk factors for the development of this disease, and stress can exacerbate inflammation and induce disease relapses 23,[41][42][43] . Indeed, other authors have noted that patients with CD or UC experience a higher incidence of emotional disorders than the general population and that depression and anxiety can influence the prognosis and severity of these diseases 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Ein RCT untersuchte die Effekte eines Programms zur Atmung, Bewegung und Meditation (BBMW) im Vergleich zu einer Edukationsgruppe auf physiologische und psychologische Symptome bei 29 Patienten mit CED [760]. Die Studie kam zu dem Ergebnis, dass BBMW durchgeführt werden kann, da es zu positiven Prä-post-Effekten führt.…”
Section: Hintergrundunclassified
“…123 In a randomized trial of 29 patients with IBD assigned to the Breath-Body-Mind Workshop (BBMW) (breathing, movement, and meditation) or an educational seminar, participation in the workshop was associated with improvements in psychological and physical symptoms, quality of life, and C-reactive protein levels. 124 Other studies have used guided imagery with relaxation training and solution-focused therapy (SFT) to demonstrate improvements in fatigue and quality of life in patients with IBD. 125130 IBD patients with high levels of perceived stress may benefit more from this therapy than those without, as demonstrated in a trial by Jedel et al .…”
Section: Stressmentioning
confidence: 99%